Robot-assisted early mobilization of intensive care patients: a feasibility study protocol - Angelika Warmbein; Ines Schroeder; Amrei Mehler-Klamt; Ivanka Rathgeber; Jana Huber; Christina Scharf; Lucas Hübner; Marcus Gutmann; Johanna Biebl; Andreas Lorenz; Eduard Kraft; Michael Zoller; et al. (Pilot and Feasibility Studies, 2022)
Abstract Background Early mobilization positively influences the outcome of critically ill patients, yet in clinical practice, the implementation is sometimes challenging. In this study, an adaptive robotic assistance system will be used for early mobilization in intensive care units. The study aims to evaluate the experience of the mobilizing professionals and the general feasibility of implementing robotic assistance for mobilization in intensive care as well as the effects on patient outcomes as a secondary outcome. Methods The study is single-centric, prospective, and interventional and follows a longitudinal study design. To evaluate the feasibility of robotic-assisted early mobilization, the number of patients included, the number of performed VEM (very early mobilization) sessions, and the number and type of adverse events will be collected. The behavior and experience of mobilizing professionals will be evaluated using standardized observations (n > 90) and episodic interviews (n > 36) before implementation, shortly after, and in routine. Patient outcomes such as duration of mechanical ventilation, loss of muscle mass, and physical activity will be measured and compared with a historical patient population. Approximately 30 patients will be included. Discussion The study will provide information about patient outcomes, feasibility, and the experience of mobilizing professionals. It will show whether robotic systems can increase the early mobilization frequency of critically ill patients. Within ICU structures, early mobilization as therapy could become more of a focus. Effects on the mobilizing professionals such as increased motivation, physical relief, or stress will be evaluated. In addition, this study will focus on whether current structures allow following the recommendation of mobilizing patients twice a day for at least 20 min. Trial registration ClinicalTrials.gov, NCT05071248 . Date: 2021/10/21